Judul Artikel: Judul Artikel - Wibowo, Mohamad Reza; Rizal , Bayu Thomi (Jurnal Porkes, 2025)
This study aims to analyze the effect of athletic learning media modifications on improving students' affective learning outcomes. The research method uses quantitative with quasi experimental design. The research population is 58 students using the total sampling technique. This research instrument uses a questionnaire. Kolmogorov-Smirnov with SPSS 26 shows the sig value. The results of the Kolmogorov smirnov and Shapiro Wilk tests show a significant value of the control class of 0.264> 0.05 and the control class of 0.098> 0.05 affective learning outcomes in throwing number athletic games, so it is concluded that the residual values are both normally distributed. in the low category as many as 3 students (11%) and in the medium category as many as 25 students (89%). While the categorization of affective results of student learning in the experimental class after the treatment of athletic throwing games in the moderate category was 14 students (14%) and the high category was 24 students (86%). The results of the research hypothesis significance value of 0.000 is smaller than 0.05, it can be concluded that there is a significant difference in the control class and experimental class post so that H0 is rejected and Ha is accepted. Hypothesis testing in this study shows that the modification of learning media for athletic throwing numbers is effective on the affective learning outcomes of fifth grade students of Teladan Suci Islamic Elementary School.